Touch choices : investing in health for development : experiences from national follow-up the Commission on Macroeconomics and Health - Spinaci, Sergio...[et al] (WHO GenevaCH, 2006)
Presents country experiences in developing and shaping work to address long-term planning for the health sector. Identifies areas of action to which the national commissions have contributed. Clarifies the most intractable challenges that have impeded faster health progress, and gives concrete examples of how countries have started to address them through an integrated approach to health sector development and financing.